Pentecostal churches in transition : analysing the developing ecclesiology of the Assemblies of God in Australia - Clifton, Shane (Global Pentecostal and Charismatic studies ;, 2009)
This book develops an ecclesiological method used to describe and analyse the transitions in culture and structure of Australian Pentecostal churches during the course of the twentieth century. These changes provide a case study of global developments in Pentecostalism.